Enhanced dielectric permittivity in poly (vinylidene) fluoride/multiwalled carbon nanotubes nanocomposite thin films fabricated by pulsed laser deposition - Chanmal, Chetan; Deo, Meenal S.; Jog, Jyoti Prakash (Applied Surface Science, 2011)
The fabrication of high quality thin films of poly (vinylidene fluoride) embedded with multiwalled carbon nanotubes using pulsed laser deposition technique is reported. The prepared films were characterized for structural, morphology and dielectric properties. The morphology analysis revealed uniform dispersion of multiwalled carbon nanotubes throughout the polymer matrix. X-ray diffraction results suggested that the poly (vinylidene fluoride) film is in amorphous phase while addition of multiwalled carbon nanotubes showed presence of crystalline peaks in the nanocomposites films. It was interesting to note that the nanocomposite films exhibits significant enhancement of the ferroelectric beta-phase as evidenced by the X-ray diffraction and Fourier transform infrared spectroscopy results. The dielectric analysis shows a remarkable enhancement in the dielectric permittivity of nanocomposites with lower loss and conductivity level. The results can be attributed to the formation of minicapacitor network and relatively higher percolation threshold in the nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric permittivity; Ferroelectric polymer; Percolation threshold; pulsed laser deposition; Thin films